Pengaruh Model Student Fasilitator and Explaining Terhadap Kemampuan Menulis Materi Teks Prosedur Siswa Kelas XI MA Subulussalam Sriwangi - Ade Messy Indriani; Suryani Suryani; Sugiarti Sugiarti (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
Students' understanding of the linguistic principles that govern procedural texts, lack of teacher interest, and ineffective implementation of learning strategies were the impetus for conducting this research. The aim of this research is to provide an overview to class This research uses a quantitative research approach, more specifically a pre-test posttest control group design. Pre-test and post-test evaluations were carried out on both groups. The research sample consisted of 62 students, consisting of 30 class XI.B students as the experimental group and 32 class XI.C students as the control group. This research uses various data acquisition methods, such as documentation, written assessment, and observation. The t-test with paired sample significance levels was implemented in the SPSS version 22 computer program as part of the data analysis method. The results of the t-test carried out at a significance level of 0.05 show that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Regarding procedure texts, the Student Facilitator and Explain methodology has a big influence on the writing ability of MA Subullusalam Sriwangi class XI students.